Women's voices: the lived experience of HIV-positive women in the postpartum period at the University of Gondar comprehensive specialized referral hospital, Ethiopia: a phenomenological study - Workie Zemene Worku; Telake Azale; Tadesse Awoke Ayele; Dawit Kassahun Mekonnen (BMC, 2023)
Abstract Background Pregnancy and the postpartum period are incredibly challenging for women living with the Human Immune Deficiency Virus (HIV) due to the multidimensional influence of HIV infection. These women experience the challenges of navigating pregnancy and motherhood while living with HIV. It is poorly understood how women living with HIV (WLWH) experience pregnancy and postpartum. Therefore, the current study aimed to explore the lived experience of pregnancy and postpartum among women living with HIV. Methods A phenomenological qualitative study design was employed. A semi-structured, interview guide was used to conduct in-depth interviews with HIV-positive postpartum women from April to May 2022. All interviews were recorded using a voice recorder and note was taken. The collected data were transcribed and translated into English for analysis. Inductive thematic analysis was applied to analyze the data. Results Six main themes about the lived experience of women living with HIV were identified: (1) Fear and distress related to maternal and child Health, (2) HIV status self-disclosure dilemma, (3) Courage and commitment of HIV-positive women to prevent HIV, (4) Challenges faced and coping mechanisms used by HIV-positive women, (5) Health care providers and HIV-positive women interaction, and (6) Solution from their voices. Conclusion HIV infection also has a multidimensional impact on women's life during pregnancy and postpartum. The findings of this study improve our understanding of the lived experience of HIV-positive women while pregnant and in the postpartum period. These women's descriptions showed that they have been experiencing various challenges that are not often addressed in antenatal clinics, such as distress and uncertainties related to vertical transmission of HIV. These women need specialized support and all-encompassing care to have a healthy pregnancy and postpartum period. Moreover, it is essential to understand the circumstances of women's lives, their relationships with others, and their decision-making processes. Healthcare professionals and other responsible bodies working with women living with HIV should encourage and support these mothers to appraise and maintain their commitment to protecting their children from acquiring HIV infection and maintaining their Health to the maximum to raise their children.